Analysis of the De Ritis ratio in different diseases: an observation in a tertiary care hospital - Ray, Tanisha; Roy, Asitava; Das, Satadal (International Journal of Research in Medical Sciences, 2025)
Background: One useful biomarker for hepatic and extra-hepatic disorders is the De Ritis ratio of serum aspartate aminotransferase/ alanine aminotransferase (AST/ALT). There is growing evidence that it affects the prognosis of diseases related to the heart, metabolism, nervous system, and kidneys. In a tertiary care context, this study sought to assess its variation among age groups and systemic disorders. Methods: Over the course of two months in 2025, a cross-sectional study was carried out at Peerless Hospital in Kolkata. There were 25 controls and 344 cases. Clinical diagnosis was used to categorize participants into groups related to gastrointestinal, cardiovascular, metabolic, neurological, kidney, and gynaecological conditions. The De Ritis ratio was computed and AST and ALT levels were tested. Data were stratified by age and analysed using Pearson correlation. Results: The De Ritis ratio was elevated in all disease groups compared to controls. Cardiovascular patients aged between 31-60 years had the highest ratios. Metabolic, gastrointestinal, and neurological disorders showed progressive increases with age. Kidney disease (KD) patients had the highest ratios in elderly groups. Strong positive correlations were observed between gastrointestinal and neurological (r=0.95, p<0.00001), and between metabolic and neurological groups (r=0.75, p=0.0047). A strong negative correlation existed between cardiovascular and metabolic groups (r=-0.76, p=0.0044). Conclusions: The De Ritis ratio’s wide range of applications beyond hepatology is supported by the notable variance it exhibits with age and disease type. Our study demonstrates that it could be a helpful prognostic marker for a variety of systemic diseases.